Remitan dan Dampaknya dalam Kehidupan Masyarakat Desa Cabawan Kecamatan Margadana Tegal - Jawa Tengah (Dimensi Ekonomi, Sosial, dan Budaya) - Maria Sri Rahayu (PIRAMIDA, 2008)
Population mobility for some people is one of strategies of ruralhouseholds to improve their prosperity, and to make and increase their income.The reason why the tendency of mobility is moving forward to the urban area isbecause the economic condition of the rural area is not answering a demand ofproper living of the society. It is also because the urban area is offering morepromising and growing informal sectors such as the merchandising. Thepopulation mobility from the rural to the urban area result a dependabilitybetween the village and the city since the immigrants is sending their income totheir family at the hometown. Remittance, according to Curson, is a transfer ofmoney, goods, and development ideas from the urban area to the rural area, andis one of instruments of the social and economy changing on the way of living of asociety.This research is held at Cabawan Village, Margadana Subdistrict, TegalMunicipality, Central Java Province (from 1997 to 1998). Cabawan Village ischosen upon a consideration that the Cabawan society is a remittee since themajority of populations (77.9%) are food-mongers who have a Warteg business inJakarta and nearby cities, so the mean of support of the society is stronglydepending on the remittance from the food-mongers (Warteg businessman). Thisresearch is describing about a strong interdependence between the food-mongersand their families at their hometown, which is implemented in the form ofremittance that has a particular effect on the villagers’ way of living both in theaspects of economic, social, and cultural.The result of this research suggest that a remittance is having a veryimportant role in the way of living of Cabawan villagers since the food-mongerswho have a Warteg business in Jakarta and nearby cities is having a significantcontribution on the mean of support of the society. The majority of the Cabawanvillagers are strongly depending on the remittance. A quite significant amount ofremittance from the city to a village is resulting in an advancement andimprovement on the rural economic, changing on the social behavior in thesociety life style and way of living, and also has a significant effect on theproductive manpower in rural area.